2020
DOI: 10.1128/mbio.00735-20
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Diversity of Staphylococcus aureus Isolates from Cystic Fibrosis Patient Lung Infections and Their Interactions with Pseudomonas aeruginosa

Abstract: Staphylococcus aureus has recently overtaken Pseudomonas aeruginosa as the most commonly recognized bacterial pathogen that infects the respiratory tracts of individuals with the genetic disease cystic fibrosis (CF) in the United States. Most studies of S. aureus in CF patient lung infections have focused on a few isolates, often exclusively laboratory-adapted strains, and how they are killed by P. aeruginosa. Less is known about the diversity of S. aureus CF patient lung isolates in terms of both their virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 93 publications
7
59
0
1
Order By: Relevance
“…A study of S. aureus strains from children with atopic dermatitis and chronic staphylococcal skin infection did not reveal many strains with agr mutation, and the expression of toxins was highly variable, as was their induction of cytokines [3]. Surveys of clinical strains from a variety of sites indicate that there are relatively few loss-of-function SNPs in major virulence genes, as might be expected, but many strains had accrued mutations or changes in the levels of expression of metabolic genes [3,[10][11][12].…”
Section: Adaptive Metabolic Changes During Chronic S Aureus Infectionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study of S. aureus strains from children with atopic dermatitis and chronic staphylococcal skin infection did not reveal many strains with agr mutation, and the expression of toxins was highly variable, as was their induction of cytokines [3]. Surveys of clinical strains from a variety of sites indicate that there are relatively few loss-of-function SNPs in major virulence genes, as might be expected, but many strains had accrued mutations or changes in the levels of expression of metabolic genes [3,[10][11][12].…”
Section: Adaptive Metabolic Changes During Chronic S Aureus Infectionmentioning
confidence: 98%
“…Such adaptive changes may be genetic and correlate with the accumulation of single nucleotide polymorphisms (SNPs) in strains harvested over time from sites of chronic infection [3,10,11]. Over the course of infection, clinical isolates of S. aureus often have altered expression of toxins [12] that is associated with mutations in central regulatory genes such as the agr, sar and codY loci [11,13,14]. Perhaps more commonly, adaptive change is at the level of transcriptional regulation, enabling the microorganisms to rapidly adapt to different metabolic modes, as reflected by planktonic versus sessile/biofilm lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…Such molecules constitute a new avenue for cellular signaling that the host and/or pathogen could leverage to their benefit during infection. These systems become even more complex in the context of polymicrobial infections, a common occurrence with P. aeruginosa and S. aureus in the lungs of CF patients (111)(112)(113). With the additional layering of another organism, the potential number of molecules and interactions increases exponentially.…”
Section: Host-pathogen Metabolic Crosstalkmentioning
confidence: 99%
“…A recent study has shed some light on the potential reason for the disparity in these studies. Sixty-four S. aureus clinical isolates from CF patients were tested for their ability to interact with P. aeruginosa and ranged from highly sensitive to completely tolerant to P. aeruginosa [156]. Many studies have now reported that long-term co-adaption of these two pathogens results in a more commensal, cooperative relationship [154,157,158].…”
Section: P Aeruginosa and S Aureus Interactionsmentioning
confidence: 99%